Multilayer electronic component

By controlling the proportion and structure of dielectric grains in a multi-layer ceramic capacitor, especially the distribution of nano-domain and local polarization regions, the dielectric performance improvement problem in the prior art is solved, and efficient dielectric performance improvement and low dielectric loss are achieved.

JP2025040936APending Publication Date: 2025-03-25SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024097190
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-12-29
Filing Date
2024-06-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

While the existing multi-layer ceramic capacitors increase the thickness of the dielectric layer, it is difficult to effectively improve the dielectric performance, especially when the dielectric layer size or grain size remains unchanged.

Method used

By controlling the ratio of the first dielectric grain to the second dielectric grain in the capacitance forming part of the multi-layer ceramic capacitor, the first dielectric grain contains a nano-domain of 10 nm to 100 nm, and the second dielectric grain contains a locally polarized region less than 10 nm, and ensuring that the number of the first dielectric grain accounts for more than 50% of the total number.

Benefits of technology

The dielectric performance of multi-layer ceramic capacitors is significantly improved, the dielectric loss is reduced, and the dielectric performance is further optimized by controlling the microstructure of the domain structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040936000001_ABST
    Figure 2025040936000001_ABST
Patent Text Reader

Abstract

To provide a multilayer electronic component in which a dielectric characteristic is improved; the dielectric characteristic is improved in the same size dielectric layer or the same size dielectric crystal particle; and the dielectric characteristic is improved by controlling a fine structure of a domain structure of the dielectric crystal particle.SOLUTION: A multilayer electronic component according to an embodiment of the present invention contains: a main body containing a dielectric layer containing a plurality of dielectric crystal particles and a capacitance formation part that contains an internal electrode alternately laminated with the dielectric layer; and an external electrode arranged onto the main body. The plurality of dielectric crystal particles contain: a first dielectric crystal particle containing a nano domain of a domain having a long diameter of 10nm or more and less than 100nm, and a second dielectric crystal particle containing a local polarization section of a domain region having the long diameter of less than 10nm. When the number of the first dielectric crystal particle contained in the capacitance formation part is ND, and the number of the second dielectric crystal particle contained in the capacitance formation part is RD, a relationship of 50%<ND / (ND+RD) is satisfied.SELECTED DRAWING: Figure 6a
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multilayer electronic component. [Background technology]

[0002] Multi-Layered Ceramic Capacitor (MLCC), a type of multi-layered electronic component, is a chip-type capacitor that is mounted on the printed circuit boards of various electronic products such as visual devices such as liquid crystal displays (LCDs) and plasma display panels (PDPs), computers, smartphones, and mobile phones to charge and discharge electricity.

[0003] Such multilayer ceramic capacitors have the advantages of being small yet high capacitance and easy to mount, and can be used as components of various electronic devices. As various electronic devices such as computers and mobile devices become smaller and have higher output, there is an increasing demand for multilayer ceramic capacitors to be smaller and have higher capacitance.

[0004] Meanwhile, as development of high-capacity multilayer ceramic capacitors progresses, research is being conducted in the direction of making the dielectric layer thinner and thinner. As the limit of how thin the dielectric layer can be made approaches, research is being conducted to improve the dielectric properties using other mechanisms. Among these, it has been revealed that one factor that can affect the dielectric properties is the control of polarization properties using an external electric or magnetic field. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Patent Application Publication No. JPWO2013-146303 Summary of the Invention

Problems to be Solved by the Invention

[0006] One of the various problems to be solved by the present invention is to provide a multilayer electronic component with improved dielectric properties.

[0007] One of the various problems to be solved by the present invention is to provide a multilayer electronic component with improved dielectric properties for a dielectric layer of the same size or dielectric crystal grains of the same size.

[0008] One of the various problems to be solved by the present invention is to provide a multilayer electronic component with improved dielectric properties by controlling the fine structure of the domain structure of dielectric crystal grains.

[0009] However, the various problems to be solved by the present invention are not limited to the above-described content, and can be more easily understood in the process of describing specific embodiments of the present invention.

Means for Solving the Problems

[0010] A multilayer electronic component according to an embodiment of the present invention includes a main body including a dielectric layer containing a plurality of dielectric crystal grains and a capacitance forming portion including internal electrodes laminated alternately with the dielectric layer, and external electrodes disposed on the main body. The plurality of dielectric crystal grains include first dielectric crystal grains including nanodomains of domain regions having a major axis of 10 nm or more and less than 100 nm, and second dielectric crystal grains including local polarization regions of domain regions having a major axis of less than 10 nm. When the number of first dielectric crystal grains included in the capacitance forming portion is ND and the number of second dielectric crystal grains included in the capacitance forming portion is RD, 50% < ND / (ND + RD) can be satisfied.

Effects of the Invention

[0011] One of the various effects of the present invention is to improve the dielectric properties of the multilayer electronic component.

[0012] One of the various advantages of the present invention is that it improves the dielectric properties of a multilayer electronic component for dielectric layers of the same size or dielectric grains of the same size.

[0013] One of the various advantages of the present invention is that it improves the dielectric properties of multilayer electronic components by controlling the fine structure of the domain structure of the dielectric crystal grains.

[0014] However, the various yet significant advantages and effects of the present invention are not limited to the above, and can be more easily understood in the course of describing specific embodiments of the present invention. [Brief description of the drawings]

[0015] [Figure 1] 1 is a schematic perspective view of a multilayer electronic component according to an embodiment of the present invention; [Diagram 2] 2 is a schematic exploded perspective view showing a laminated structure of internal electrodes; FIG. [Diagram 3] 2 is a schematic cross-sectional view taken along line II' of FIG. 1. [Figure 4] 2 is a schematic cross-sectional view taken along line II-II' in FIG. 1. [Diagram 5] 4 is a schematic diagram showing an enlarged view of region P in FIG. 3. [Figure 6a] 1 is a schematic representation of a dielectric grain containing nano-domains. [Figure 6b] 1 is a schematic representation of a dielectric grain containing locally polarized regions (PNRs). [Figure 7a] 13 is an image showing a domain region measured by an AFM measuring device when an electric field is applied to the dielectric microstructure of the comparative example. [Figure 7b] 1 is an image showing a domain region measured by an AFM measuring device when an electric field is applied to a dielectric microstructure according to an embodiment of the present invention. [Figure 8a] 13 is a diagram illustrating, by a program, nano-domain regions when an electric field is applied to a dielectric microstructure of a comparative example. [Figure 8b]1 is a graph showing, by a program, nano-domain regions when an electric field is applied to a dielectric microstructure of an embodiment. [Figure 9] 1 is a graph showing dielectric capacitance as a function of voltage in a comparative example and an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, the embodiments of the present invention will be described with reference to specific embodiments and the accompanying drawings. However, the embodiments of the present invention can be modified into several other forms, and the scope of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those skilled in the art. Therefore, the shapes and sizes of elements in the drawings may be enlarged or reduced (or highlighted or simplified) for clearer explanation, and elements indicated by the same reference numerals in the drawings are the same elements.

[0017] In addition, in the drawings, parts that are not relevant to the description are omitted in order to clearly explain the present invention, and the size and thickness of each component shown in the drawings are arbitrarily shown for convenience of explanation, so the present invention is not necessarily limited by the drawings. Furthermore, components having the same function within the same concept may be described using the same reference numerals. Furthermore, throughout the specification, when a part "includes" a certain component, it does not mean that the part excludes other components, but that the part may further include other components, unless otherwise specified to the contrary.

[0018] In the drawings, the first direction can be defined as the stacking direction or thickness (T) direction, the second direction can be defined as the length (L) direction, and the third direction can be defined as the width (W) direction.

[0019] Multilayer Electronic Components FIG. 1 schematically shows a perspective view of a multilayer electronic component according to an embodiment of the present invention. FIG. 2 schematically shows an exploded perspective view showing the laminated structure of internal electrodes. FIG. 3 schematically shows a cross-sectional view taken along line I-I' of FIG. 1. FIG. 4 schematically shows a cross-sectional view taken along line II-II' of FIG. 1. FIG. 5 schematically shows an enlarged view of the P region in FIG. 3. FIG. 6a schematically shows a dielectric crystal grain containing nanodomains. FIG. 6b schematically shows a dielectric crystal grain containing a local polarization region (PNR).

[0020] Hereinafter, with reference to FIGS. 1 to 6b, a multilayer electronic component according to an embodiment of the present invention will be described in detail. However, although a multilayer ceramic capacitor will be described as an example of the multilayer electronic component, the present invention can also be applied to various electronic products using a dielectric composition, such as inductors, piezoelectric elements, varistors, or thermistors.

[0021] A multilayer electronic component 100 according to an embodiment of the present invention includes a main body 110 including a dielectric layer 111 containing a plurality of dielectric crystal grains 10, and a capacitance forming portion Ac including internal electrodes 121 and 122 laminated alternately with the dielectric layer 111, and external electrodes 131 and 132 disposed on the main body 110. The plurality of dielectric crystal grains 10 include first dielectric crystal grains 20 containing nanodomains in a domain region having a major axis of 10 nm or more and less than 100 nm, and second dielectric crystal grains 30 containing local polarization regions (polar nano regions, PNRs) in a domain region having a major axis of less than 10 nm. When the number of the first dielectric crystal grains 20 included in the capacitance forming portion Ac is ND and the number of the second dielectric crystal grains 30 included in the capacitance forming portion Ac is RD, 50% < ND / (ND + RD) can be satisfied.

[0022] The present invention can provide a dielectric composition, dielectric crystal grains, dielectric microstructure, dielectric layer, or multilayer electronic component having improved dielectric properties for the same or similar crystal grain sizes by controlling the ratio of the number of domains having different sizes.

[0023] The body 110 may include dielectric layers 111 and internal electrodes 121 and 122 that are alternately laminated.

[0024] More specifically, the main body 110 may include a capacitance forming portion Ac that is disposed inside the main body 110 and includes first internal electrodes 121 and second internal electrodes 122 that are alternately arranged facing each other across the dielectric layer 111 to form a capacitance.

[0025] Although there is no particular limitation on the specific shape of the body 110, the body 110 may be hexahedral or a similar shape as shown in the figure. Due to shrinkage of ceramic particles contained in the body 110 during the firing process, the body 110 may not be a hexahedral shape with perfectly straight lines, but may be substantially hexahedral.

[0026] The main body 110 may have a first surface 1 and a second surface 2 facing each other in a first direction, a third surface 3 and a fourth surface 4 connected to the first surface 1 and the second surface 2 and facing each other in the second direction, and a fifth surface 5 and a sixth surface 6 connected to the first surface 1, the second surface 2, the third surface 3 and the fourth surface 4 and facing each other in the third direction.

[0027] The plurality of dielectric layers 111 forming the body 110 are in a sintered state, and the boundaries between adjacent dielectric layers 111 may be integrated to such an extent that they are difficult to see without using a scanning electron microscope (SEM).

[0028] The raw material for forming the dielectric layer 111 is not limited as long as a sufficient capacitance can be obtained. In general, a perovskite (ABO3)-based material can be used, such as a barium titanate-based material, a lead complex perovskite-based material, or a strontium titanate-based material. The barium titanate-based material can include BaTiO3-based ceramic particles, and examples of the ceramic particles include BaTiO3, BaTiO3 partially solid-dissolved with Ca (calcium), Zr (zirconium), etc. 1-x Ca x )TiO3(0 <x<1)、Ba(Ti1-y Ca y )O3 (0 < y < 1), (Ba 1-x Ca x )(Ti 1-y Zr y )O3 (0 < x < 1, 0 < y < 1) or Ba(Ti 1-y Zr y )O3 (0 < y < 1), etc. can be mentioned.

[0029] In addition, various ceramic additives, organic solvents, binders, dispersants, etc. can be added to the raw materials for forming the dielectric layer 111 according to the purpose of the present invention to particles such as barium titanate (BaTiO3).

[0030] In addition, since the dielectric layer 111 can be formed using a dielectric material such as barium titanate (BaTiO3), it can contain a dielectric fine structure after firing. The dielectric fine structure can include a plurality of dielectric crystal grains 10, a dielectric grain boundary disposed between the adjacent dielectric crystal grains 10, and a dielectric triple point disposed at a point where three or more of the dielectric grain boundaries meet, and each can include a plurality.

[0031] In addition, the plurality of dielectric crystal grains 10 can include a first dielectric crystal grain 20 including a nano domain in a domain region with a major axis of 10 nm or more and less than 100 nm, and a second dielectric crystal grain 30 including a local polarization region (polar nano region, PNR) in a domain region with a major axis of less than 10 nm. On the other hand, the second dielectric crystal grain 20 including the local polarization region (PNR) may not be easy to observe the domain region as it includes a domain region with a major axis of less than 10 nm, and furthermore, since the direction arrangement of polarization is not clear, a domain wall may be difficult to form, and thus the observation of the domain wall may also not be easy. Accordingly, in the present invention, when there is no domain region, that is, a domain region with a size of 0 nm is also interpreted as a local polarization region, and the dielectric crystal grain including this is also described as corresponding to the second dielectric crystal grain 20.

[0032] In the present invention, the term "domain region" refers to a certain region where the same polarization direction is concentrated, and the term "domain wall" refers to a region having a finite thickness where the polarization direction changes abruptly between adjacent domain regions. The term "polarization direction" refers to a direction in which charges are uniformly arranged, and may be expressed as a direction from negative charges to positive charges based on charges, and generally, charges or polarization directions may be arranged in a direction when an external electric field is applied, but is not limited thereto. The term "domain size" refers to a major diameter passing through the center of a domain region observed through a domain (polarization) measurement device.

[0033] The domain region can be observed using the following measurement equipment, and the measurement equipment can be, for example, an atomic force microscope (AFM), a piezoelectric force microscope (PFM), a scanning electron microscope (SEM), a transmission electron microscope (TEM), a scanning transmission electron microscope (STEM), or a polarization microscope (PM), or the like, but is not limited thereto.

[0034] Meanwhile, the first dielectric crystal grains 20 and the second dielectric crystal grains 30 may include at least one type of domain region, and a domain wall may be disposed between adjacent domain regions.

[0035] For example, the first dielectric grain 20 can include at least one nanodomain 21 but no localized polarization region 31 and the second dielectric grain 30 can include at least one localized polarization region 31 but no nanodomain 21.

[0036] Also, the first dielectric crystal grains 20 may include three or more different nanodomains 21, and may include two or more domain walls 22 disposed between adjacent nanodomains 21, and at least two of the domain walls 22 may be non-parallel. Alternatively, at least two major diameter directions of the nanodomains 21 may be non-parallel.

[0037] Here, the meaning of the major diameter directions of the domain walls or domain regions being not parallel may mean that the angle difference between the two lines calculated by assuming that the two domain walls are straight lines exceeds 10°, or that the angle difference between the major diameter directions of the two domain regions exceeds 10°, but is not particularly limited thereto.

[0038] The second dielectric crystal grains 30 may have a polarization direction 33 arranged randomly or may include a local polarization region (PNR) of a domain region having a constant polarization direction 33 arrangement, but is not particularly limited thereto, and when the polarization direction 33 is arranged randomly, the second dielectric crystal grains 30 may not include a local polarization region (PNR) and may not include a domain wall. When there is no domain region having a constant polarization direction 33 arrangement, the entire second dielectric crystal grains 30 may be expressed as a local polarization region 31 of a domain region having polarization, but this may not correspond to the size of the domain region described in the present invention. In other words, the size of the domain region in the present invention may mean a closed region surrounded by a domain wall.

[0039] On one hand, when the number of the first dielectric crystallites 20 included in the capacitance forming portion Ac is ND and the number of the second dielectric crystallites 30 included in the capacitance forming portion Ac is RD, 50% < ND / (ND + RD) can be satisfied, and preferably 66% < ND / (ND + RD) can be satisfied. This can mean that the number ND of the first dielectric crystallites 20 is even larger than the number RD of the second dielectric crystallites 30 included in the capacitance forming portion Ac (RD < ND), and preferably, the number ND of the first dielectric crystallites 20 can mean that it exceeds twice the number RD of the second dielectric crystallites 30 (2×RD < ND).

[0040] When the numbers ND and RD of the first dielectric crystallites 20 and the second dielectric crystallites 30 included in the capacitance forming portion Ac are observed with an atomic force microscope (AFM) for a cross-section of 0.8 μm × 0.8 μm in the first and second directions at the center in the third direction of the main body 110, the number of the first dielectric crystallites 20 including nanodomains with a major axis of the domain region being 10 nm or more and less than 100 nm is regarded as ND, and the number of the second dielectric crystallites 30 including local polarization regions (PNRs) with a major axis of the domain region being less than 10 nm is regarded as RD, and the number of each dielectric crystallite can be counted. Here, the domain region can be observed in the capacitance forming portion Ac, specifically, it can be observed in the dielectric layer 111 included in the capacitance forming portion Ac, and more specifically, it can be observed in a plurality of dielectric crystallites 10 included in the dielectric layer 111.

[0041] The number ND of the first dielectric crystallites 20 and the number RD of the second dielectric crystallites 30 can be obtained by the following method, but it is not particularly limited thereto.

[0042] First, regarding the cross-sectional area region of the dielectric layer 111 in the cross-sections in the second and third directions at the center of the main body 110 in the first direction, observe it in the piezoelectric response force microscope (PFM) analysis mode of the atomic force microscope (AFM). At this time, apply a voltage in a direction perpendicular to the cross-sectional area, and measure the domain region in a direction horizontal to the internal electrodes 121 and 122 using a constant frequency. By such a measurement method, it is possible to observe the domain region having a polarization direction corresponding to the direction horizontal to the internal electrodes 121 and 122. Here, at least two observed domain regions may have a 180° difference in the polarization direction.

[0043] When observing the dielectric crystal grains 10 by applying a constant voltage of a constant frequency with an atomic force microscope (AFM), it can be confirmed that a plurality of domain regions arranged in a certain polarization direction are observed. The domain region with a major axis length of 10 nm or more and less than 100 nm can be regarded as the nano-domain 21, and the domain region with a major axis length of less than 10 nm can be regarded as the local polarization region 31. At this time, the dielectric crystal grains containing the nano-domain 21 can be the first dielectric crystal grains 20, and the dielectric crystal grains containing the local polarization region 31 can be the second dielectric crystal grains 30. And the numbers of the first dielectric crystal grains 20 and the second dielectric crystal grains 30 observed by classifying according to the above criteria can be ND and RD respectively.

[0044] When the capacitance forming part Ac satisfies 50% < ND / (ND + RD), the dielectric characteristics can be improved for the same or similar sizes of the dielectric crystal grains 10, and there may be a low dissipation factor (DF). When 66% < ND / (ND + RD) is satisfied, the dielectric characteristics can be further improved for the same or similar sizes of the dielectric crystal grains 10, and the dielectric loss (DF) may be even lower.

[0045] When the capacitance forming part Ac satisfies ND / (ND + RD) ≤ 50%, there may be a risk that the improvement of the dielectric characteristics cannot be excellent for the same or similar sizes of the dielectric crystal grains 10.

[0046] On the other hand, the capacitance forming portion Ac includes a plurality of nano-domains 21, and the percentage of the total cross-sectional area of ​​the regions of the plurality of nano-domains 21 with respect to the cross-sectional area of ​​the capacitance forming portion Ac can be 10% or more.

[0047] Here, the total cross-sectional area of ​​the multiple nanodomains 21 may refer to the total area of ​​the nanodomains 21 observed when the capacitance forming portion Ac is observed with equipment capable of measuring the domain area.

[0048] When the percentage of the total cross-sectional area of ​​the nano-domains 21 regions to the cross-sectional area of ​​the capacitance forming portion Ac is 10% or more, the dielectric characteristics for the same or similar size of the dielectric crystal grains 10 can be improved.

[0049] If the percentage of the total cross-sectional area of ​​the multiple nano-domains 21 regions to the cross-sectional area of ​​the capacitance forming portion Ac is less than 10%, there is a risk that excellent improvement in the dielectric characteristics for the same or similar sizes of the dielectric crystal grains 10 cannot be achieved.

[0050] In an embodiment of the present invention, the average diameter of the plurality of dielectric crystal grains 10 included in the dielectric layer 111 may be 100 nm or more and 300 nm or less. In this case, the plurality of dielectric crystal grains 10 may be a concept including the first dielectric crystal grains 20 and the second dielectric crystal grains 30.

[0051] When the average diameter of the plurality of dielectric crystal grains 10 satisfies the range of 100 nm or more and 300 nm or less, nanodomains 21 can be easily generated, and the effect of improving the dielectric characteristics due to the ratio of the numbers of the first dielectric crystal grains 20 and the second dielectric crystal grains 30 can be more excellent.

[0052] The average diameter of the dielectric crystal grains 10 included in the dielectric layer 111 may mean the average diameter of the dielectric crystal grains 10 observed in a corresponding region when a cross-section in the first and second directions is observed at the center of the third direction of the body 110 using a scanning electron microscope (SEM) or an atomic force microscope (AFM), and here, the diameter of the dielectric crystal grains 10 may correspond to a diameter calculated using the "Image J" program. For example, the diameter of one of the dielectric crystal grains 10 may mean the average value of the long diameter and the short diameter passing through the center of one of the dielectric crystal grains 10, and after determining the diameter of each of the dielectric crystal grains 10 in this manner, the diameters of the plurality of dielectric crystal grains 10 may be averaged again to obtain the average diameter of the plurality of dielectric crystal grains 10, which may be the average diameter of the plurality of dielectric crystal grains 10.

[0053] In this manner, the diameter of one of the first dielectric crystal grains 20 or the average diameter of a plurality of the first dielectric crystal grains 20, which will be described later, can be obtained.

[0054] On the other hand, the plurality of dielectric crystal grains 10 may include a plurality of first dielectric crystal grains 20, and the average diameter of the plurality of first dielectric crystal grains 20 may be not less than 100 nm and not more than 300 nm.

[0055] In this case, the percentage of the major diameter of one of the nano-domains 21 to the diameter of one of the first dielectric crystal grains 20 may be 26% or more.

[0056] More specifically, the percentage value of the major diameter passing through the center of one of the nano-domains 21 included in the same first dielectric crystal grain 20 relative to the diameter of one of the first dielectric crystal grains 20 may be 26% or more.

[0057] When the percentage of the size of the nanodomains 21 relative to the size of the first dielectric crystal grains 20 is 26% or more, the size of the nanodomains 21 having the same polarization direction 23 is sufficient, and the dielectric characteristics of the laminated electronic component 100 can be improved.

[0058] The thickness td of the dielectric layer 111 does not need to be particularly limited.

[0059] However, in order to more easily achieve a smaller size and higher capacity of the multilayer electronic component 100, the thickness of the dielectric layer 111 may be 0.6 μm or less, and more preferably 0.4 μm or less.

[0060] Here, the thickness td of the dielectric layer 111 may refer to the thickness td of the dielectric layer 111 disposed between the first internal electrode 121 and the second internal electrode 122.

[0061] Meanwhile, the thickness td of the dielectric layer 111 may refer to the size of the dielectric layer 111 in the first direction. In addition, the thickness td of the dielectric layer 111 may refer to the average thickness td of the dielectric layer 111, or may refer to the average size of the dielectric layer 111 in the first direction.

[0062] The average size in the first direction of the dielectric layer 111 may be measured by scanning an image of a cross-section in the first and second directions of the body 110 using a scanning electron microscope (SEM) with a magnification of 10,000. More specifically, the average size in the first direction of one dielectric layer 111 may mean an average value calculated by measuring the size in the first direction of one dielectric layer 111 at 30 equally spaced points in the second direction in the scanned image. The 30 equally spaced points may be designated as the capacitance forming portion Ac. Furthermore, if such an average value measurement is extended to 10 dielectric layers 111 to measure the average value, the average size in the first direction of the dielectric layer 111 may be further generalized.

[0063] The internal electrodes 121 and 122 may be laminated alternately with the dielectric layers 111 .

[0064] The internal electrodes 121, 122 may include a first internal electrode 121 and a second internal electrode 122, and the first internal electrode 121 and the second internal electrode 122 are alternately arranged to face each other across the dielectric layer 111 that constitutes the main body 110, and may be exposed to the third surface 3 and the fourth surface 4 of the main body 110, respectively.

[0065] More specifically, the first internal electrode 121 may be spaced apart from the fourth surface 4 and exposed through the third surface 3, and the second internal electrode 122 may be spaced apart from the third surface 3 and exposed through the fourth surface 4. A first external electrode 131 may be disposed on the third surface 3 of the body 110 and connected to the first internal electrode 121, and a second external electrode 132 may be disposed on the fourth surface 4 of the body 110 and connected to the second internal electrode 122.

[0066] That is, the first internal electrode 121 may be connected to the first external electrode 131 without being connected to the second external electrode 132, and the second internal electrode 122 may be connected to the second external electrode 132 without being connected to the first external electrode 131. In this case, the first internal electrode 121 and the second internal electrode 122 may be electrically isolated from each other by the dielectric layer 111 disposed therebetween.

[0067] Meanwhile, the body 110 may be formed by alternately stacking ceramic green sheets on which the first internal electrodes 121 are printed and ceramic green sheets on which the second internal electrodes 122 are printed, and then firing the stacked ceramic green sheets.

[0068] There are no particular limitations on the material forming the internal electrodes 121 and 122, and any material having excellent electrical conductivity can be used. For example, the internal electrodes 121 and 122 can include one or more of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof.

[0069] The internal electrodes 121 and 122 may be formed by printing a conductive paste for internal electrodes, which contains at least one of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof, on a ceramic green sheet. The method for printing the conductive paste for internal electrodes may be a screen printing method or a gravure printing method, but the present invention is not limited thereto.

[0070] On the other hand, the thickness te of the internal electrodes 121 and 122 does not need to be particularly limited.

[0071] However, in order to more easily achieve miniaturization and high capacity of the multilayer electronic component, the thickness of the internal electrodes 121, 122 may be 0.6 μm or less, and more preferably 0.4 μm or less.

[0072] Here, the thickness te of the internal electrodes 121, 122 may refer to the size of the internal electrodes 121, 122 in the first direction. In addition, the thickness te of the internal electrodes 121, 122 may refer to the average thickness te of the internal electrodes 121, 122, or may refer to the average size of the internal electrodes 121, 122 in the first direction.

[0073] The average size of the internal electrodes 121, 122 in the first direction may be measured by scanning an image of a cross-section of the body 110 in the first and second directions with a scanning electron microscope (SEM) at a magnification of 10,000. More specifically, the average size of one internal electrode in the first direction may be an average value calculated by measuring the size of one internal electrode in the first direction at 30 equally spaced points in the second direction in the scanned image. The 30 equally spaced points may be designated as the capacitance forming portion Ac. Furthermore, if such an average measurement is extended to 10 internal electrodes 121, 122 to measure the average, the average size of the internal electrodes 121, 122 in the first direction may be further generalized.

[0074] Meanwhile, the body 110 may include cover portions 112 and 113 disposed on both end surfaces in the first direction of the capacitance forming portion Ac.

[0075] Specifically, it may include a first cover part 112 arranged on one side of the capacitance forming part Ac in the first direction and a second cover part 113 arranged on the other side of the capacitance forming part Ac in the first direction, and more specifically, it may include an upper cover part 112 arranged on the upper part of the capacitance forming part Ac in the first direction and a lower cover part 113 arranged on the lower part of the capacitance forming part Ac in the first direction.

[0076] The upper cover part 112 and the lower cover part 113 may be formed by stacking a single dielectric layer 111 or two or more dielectric layers 111 in a first direction on the upper and lower surfaces of the capacitance forming part Ac, respectively, and may basically serve to prevent damage to the internal electrodes 121, 122 due to physical or chemical stress.

[0077] The upper cover part 112 and the lower cover part 113 do not include the internal electrodes 121, 122 and may include the same material as the dielectric layer 111. That is, the upper cover part 112 and the lower cover part 113 may include a ceramic material, for example, a barium titanate (BaTiO3)-based ceramic material.

[0078] On the other hand, the thickness tc of the covers 112 and 113 does not need to be particularly limited.

[0079] However, in order to more easily achieve miniaturization and high capacity of the multilayer electronic component, the thickness tc of the cover parts 112, 113 can be 100 μm or less, preferably 30 μm or less, and more preferably 20 μm or less for ultra-small products.

[0080] Here, the thickness tc of the cover parts 112, 113 may refer to the size of the cover parts 112, 113 in the first direction. In addition, the thickness tc of the cover parts 112, 113 may refer to the average thickness tc of the cover parts 112, 113, or may refer to the average size of the cover parts 112, 113 in the first direction.

[0081] The average size in the first direction of the covers 112 and 113 may be measured by scanning an image of a cross-section in the first and second directions of the body 110 with a scanning electron microscope (SEM) at a magnification of 10,000. More specifically, the average size in the first direction may be calculated by measuring the size in the first direction at 30 points equally spaced in the second direction in an image obtained by scanning one cover.

[0082] Furthermore, the average size in the first direction of the cover portion measured by the above-mentioned method may be substantially the same as the average size in the first direction of the cover portion in the cross-sections of the main body 110 in the first and third directions.

[0083] Meanwhile, side margin parts 114 and 115 may be disposed on both end surfaces of the body 110 in the third direction.

[0084] More specifically, the side margin portions 114, 115 may include a first side margin portion 114 disposed on the fifth surface 5 of the main body 110 and a second side margin portion 115 disposed on the sixth surface 6. That is, the side margin portions 114, 115 may be disposed on both end surfaces of the main body 110 in the third direction.

[0085] As shown in the figure, the side margin portions 114, 115 may refer to the areas between both ends of the first internal electrode 121 and the second internal electrode 122 in the third direction and the boundary surface of the body 110, based on the cross-sections in the first and third directions of the body 110.

[0086] The side margins 114 and 115 essentially serve to prevent damage to the internal electrodes 121 and 122 due to physical or chemical stress.

[0087] The side margin portions 114, 115 can also be formed by forming internal electrodes 121, 122 by applying a conductive paste to the ceramic green sheet except for the areas where the side margin portions 114, 115 are to be formed, and then cutting the laminated internal electrodes 121, 122 so that they are exposed on the fifth surface 5 and the sixth surface 6 of the main body 110 in order to suppress steps caused by the internal electrodes 121, 122, and then stacking a single dielectric layer 111 or two or more dielectric layers 111 in the third direction on both end surfaces in the third direction of the capacitance forming portion Ac.

[0088] The first side margin portion 114 and the second side margin portion 115 do not include the internal electrodes 121, 122, and may include the same material as the dielectric layer 111. That is, the first side margin portion 114 and the second side margin portion 115 may include a ceramic material, for example, a barium titanate (BaTiO3)-based ceramic material.

[0089] On the other hand, the width wm of the first side margin portion 114 and the second side margin portion 115 does not need to be particularly limited.

[0090] However, in order to more easily achieve miniaturization and high capacity of the laminated electronic component 100, the width wm of the first side margin portion 114 and the second side margin portion 115 can be 100 μm or less, preferably 30 μm or less, and for ultra-small products, more preferably 20 μm or less.

[0091] Here, the width wm of the side margin portions 114, 115 may refer to the size in the third direction of each of the side margin portions 114, 115. In addition, the width wm of the side margin portions 114, 115 may refer to the average width wm of the side margin portions 114, 115, or may refer to the average size in the third direction of the side margin portions 114, 115.

[0092] The average size in the third direction of the side margin portions 114, 115 may be measured by scanning an image of a cross-section in the first and third directions of the body 110 with a scanning electron microscope (SEM) at a magnification of 10,000. More specifically, it may mean an average value calculated by measuring the size in the third direction at 10 points equally spaced in the first direction in an image obtained by scanning one side margin portion.

[0093] In one embodiment of the present invention, a structure in which the ceramic electronic component 100 has two external electrodes 131, 132 is described, but the number and shapes of the external electrodes 131, 132 can be changed depending on the shape of the internal electrodes 121, 122 and other purposes.

[0094] The outer electrodes 131 and 132 may be disposed on the body 110 and connected to the inner electrodes 121 and 122 .

[0095] More specifically, the external electrodes 131, 132 may include a first external electrode 131 and a second external electrode 132 disposed on the third surface 3 and the fourth surface 4 of the body 110, respectively, and connected to the first internal electrode 121 and the second internal electrode 122, respectively. That is, the first external electrode 131 may be disposed on the third surface 3 of the body and connected to the first internal electrode 121, and the second external electrode 132 may be disposed on the fourth surface 4 of the body and connected to the second internal electrode 122.

[0096] Furthermore, the external electrodes 131, 132 may be arranged to extend over a portion of the first surface 1 and the second surface 2 of the main body 110, or may be arranged to extend over a portion of the fifth surface 5 and the sixth surface 6 of the main body 110. That is, the first external electrode 131 may be arranged over a portion of the first surface 1, the second surface 2, the fifth surface 5 and the sixth surface 6 of the main body 110, and over the third surface 3 of the main body 110, and the second external electrode 132 may be arranged over a portion of the first surface 1, the second surface 2, the fifth surface 5 and the sixth surface 6 of the main body 110, and over the third surface 3 of the main body 110.

[0097] The external electrodes 131, 132 may be formed using any material that has electrical conductivity, such as a metal, and the specific material may be determined taking into consideration electrical characteristics, structural stability, etc., and may further have a multi-layer structure.

[0098] For example, the external electrodes 131, 132 may include electrode layers 131a, 132a disposed on the body 110 and plating layers 131b, 132b disposed on the electrode layers 131a, 132a.

[0099] As a more specific example of the electrode layers 131a and 132a, the electrode layers 131a and 132a may be fired electrodes containing a conductive metal and glass, or resin-based electrodes containing a conductive metal and resin.

[0100] Also, the electrode layers 131a and 132a may be in a form in which a fired electrode and a resin-based electrode are sequentially formed on the body 110.

[0101] In addition, the electrode layers 131a and 132a may be formed by transferring a sheet containing a conductive metal onto the body 110, or may be formed by transferring a sheet containing a conductive metal onto a fired electrode.

[0102] The conductive metal used for the electrode layers 131a and 132a is not particularly limited as long as it can be electrically connected to the internal electrodes 121 and 122 to form capacitance, and may include, for example, at least one selected from the group consisting of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof. The electrode layers 131a and 132a may be formed by applying a conductive paste prepared by adding glass frit to the conductive metal particles, and then firing the paste.

[0103] The plating layers 131b and 132b can serve to improve mounting characteristics.

[0104] The type of plating layers 131b, 132b is not particularly limited, and may be a single layer plating layer 131b, 132b containing one or more of nickel (Ni), tin (Sn), silver (Ag), palladium (Pd), and alloys thereof, or may be formed of multiple layers.

[0105] As a more specific example of the plating layers 131b, 132b, the plating layers 131b, 132b may be Ni plating layers or Sn plating layers, and may be in a form in which a Ni plating layer and a Sn plating layer are sequentially formed on the electrode layers 131a, 132a, or in a form in which a Sn plating layer, a Ni plating layer, and a Sn plating layer are sequentially formed. The plating layers 131b, 132b may also include a plurality of Ni plating layers and / or a plurality of Sn plating layers.

[0106] The size of the multilayer electronic component 100 does not need to be particularly limited.

[0107] However, in order to simultaneously achieve miniaturization and high capacity, the thickness of the dielectric layers and internal electrodes must be reduced and the number of layers must be increased, so the effects of the present invention can be more pronounced in multilayer electronic components 100 having sizes of 1005 (length x width: 1.0 mm x 0.5 mm, length and width error range within ±5%) and 0603 (length x width: 0.6 mm x 0.3 mm, length and width error range within ±5%) or less.

[0108] The present invention will be described in more detail below with reference to test examples. However, these are intended to aid in the concrete understanding of the invention, and the scope of the present invention is not limited to these test examples.

[0109] (Test Example) The present invention will be described more specifically with reference to Comparative Example 1 and Example 1 as examples, but the scope of the present invention is not particularly limited thereto.

[0110] The number of dielectric crystal grains measured in an area of ​​the dielectric layer of Comparative Example 1 observed at 70,000 times magnification through a scanning electron microscope (SEM) was 502, the minimum diameter of any one dielectric crystal grain was 27.6 nm, the maximum diameter of multiple dielectric crystal grains was 499.5 nm, the average value was 184 nm, and the sample deviation (STDEV) was 82.4.

[0111] The number of dielectric crystal grains measured in an area of ​​the dielectric layer of Example 1 observed at 70,000 times magnification through a scanning electron microscope (SEM) was 545, the minimum diameter of any one of the dielectric crystal grains was 40.0 nm, the maximum diameter of the multiple dielectric crystal grains was 538.4 nm, the average value was 179 nm, and the sample deviation (STDEV) was 79.1.

[0112] When compared with Comparative Example 1, the average size of the dielectric crystal grains in Example 1 is reduced by about 3%, which corresponds to a similar size level when the error range is taken into consideration.

[0113] The following describes the method of measuring the domain region for Comparative Example 1 and Example 1. First, a voltage is applied in the piezoelectric force microscope (PFM) analysis mode of an atomic force microscope (AFM) to a 0.8 μm×0.8 μm cross-sectional area of ​​the dielectric layer 111 in the cross-section in the second and third directions at the center in the first direction of the main body 110 of Comparative Example 1 and Example 1. At this time, a Multi75E-G cantilever is used, and a voltage of drive amplitude 1V is applied in a direction perpendicular to the cross-sectional area. The measurement direction of the domain region is measured in a lateral PFM mode with a frequency of 650 kHz in a direction parallel to the Ni electrode. By this measurement method, it was possible to measure the domain region corresponding to the direction parallel to the Ni electrode. Here, a difference of 180° can be observed between the polarization directions of at least two domain regions observed.

[0114] In the piezoelectric reaction force microscope (PFM) analysis mode, information regarding the domain regions and domain wall distribution of the sample can be confirmed from the amplitude information, and information regarding the direction of polarization can be confirmed from the phase information.

[0115] More specifically, as can be seen from FIG. 7a, which is an image observed with the amplitude information in the piezoelectric reaction force microscope (PFM) analysis mode for Comparative Example 1, a first dielectric crystal grain 20 containing a plurality of nanodomains and a second dielectric crystal grain 30 containing a local polarization region can be observed within a cross-sectional area of 0.8 μm × 0.8 μm of the dielectric layer, and it can be confirmed that the number (RD) of the second dielectric crystal grains 30 is larger than the number (ND) of the first dielectric crystal grains 20 (ND < RD). At this time, the average major diameter of the plurality of observed nanodomains 21 was measured to be 70 nm or more and 80 nm or less.

[0116] Also, as can be seen from FIG. 7b, which is an image observed with the amplitude information in the piezoelectric reaction force microscope (PFM) analysis mode for Example 1, a first dielectric crystal grain 20 containing a plurality of nanodomains and a second dielectric crystal grain 30 containing a local polarization region can be observed within a cross-sectional area of 0.8 μm × 0.8 μm of the dielectric layer, and it can be confirmed that the number (ND) of the first dielectric crystal grains 20 is larger than the number (RD) of the second dielectric crystal grains 30 (RD < ND). At this time, the average major diameter of the plurality of observed nanodomains 21 was measured to be 80 nm or more and 100 nm or less.

[0117] On the other hand, in FIG. 8a, which shows an image observed with the phase information in the piezoelectric reaction force microscope (PFM) analysis mode for the same region as FIG. 7a of Comparative Example 1, using the nanodomains 21 and the domain walls 22 of the nanodomains, the domain walls 22 of the nanodomains correspond to those represented by lines, and the nanodomains 21 correspond to closed regions surrounded by the domain walls 22 of the nanodomains. Among the regions shown in the program of FIG. 8a, the area percentage of the nanodomains 21 was observed to be approximately 3%.

[0118] Fig. 8b shows an image observed with phase information in the piezoelectric reaction force microscope (PFM) analysis mode for the same region as Fig. 7b of Example 1, where the domain wall 22 of the nanodomain is represented by a line, and the nanodomain 21 corresponds to a closed region surrounded by the domain wall 22 of the nanodomain. Among the regions shown in the program of Fig. 8b, the area percentage of the nanodomain 21 was observed to be about 11%.

[0119] When the capacitance was measured for Comparative Example 1 and Example 1, it was confirmed that the capacitance of Example 1 increased by 6% compared to Comparative Example 1.

[0120] From this, it can be confirmed that in dielectric crystal grains of similar size, when the number ND of the first dielectric crystal grains 20 contained in the capacitance forming portion Ac is larger than the number RD of the second dielectric crystal grains 30 contained in the capacitance forming portion Ac (RD < ND), the capacitance is improved.

[0121] Also, among the observed regions of the dielectric layer 111, it can be interpreted that the larger the area of the nanodomain 21, the larger the number (ND) of the nanodomains 21, and thus the larger the number of the domain walls 22 of the nanodomains. Accordingly, it can be predicted that the dielectric properties can be improved.

[0122] Next, Table 1 shows the number ND of the first dielectric crystal grains 20 and the number RD of the second dielectric crystal grains 30 of Comparative Examples 2 to 3 and Examples 2 to 4 observed by the above-described method, and the ratios of these two are calculated and described as percentages, and the capacitance (nF) for each test example was measured and then described. At this time, the capacitance was measured using an LCR meter.

[0123] The average diameters of the plurality of dielectric crystal grains of Comparative Examples 2 to 3 and Examples 2 to 4 are 100 nm or more and 300 nm or less, and it was confirmed that they have dielectric crystal grains of similar size within the error tolerance range.

[0124]

Table 1

[0125] In Comparative Examples 2 to 3, it was confirmed that the number (ND) of the first dielectric crystal grains was less than or equal to the number (RD) of the second dielectric crystal grains (ND≦RD), and the capacitance did not exceed 450 nF. On the other hand, in Examples 3 to 4, it was confirmed that the number ND of the first dielectric crystal grains was larger than the number RD of the second dielectric crystal grains, and the capacitance exceeded 450 nF. More specifically, the ratio of the first dielectric crystal grains in Example 2 was 51%, and the ratio of the first dielectric crystal grains in Comparative Example 3 was 50%. It can be confirmed that the capacitance of Example 2 increased by about 5% compared to the capacitance of Comparative Example 3.

[0126] From this, it can be seen that when having similar dielectric crystal grain diameters, when the number ND of the first dielectric crystal grains is larger than the number RD of the second dielectric crystal grains (RD<ND), the capacitance is improved.

[0127] Next, Table 2 describes the measured dielectric losses (DF) of Comparative Example 2 and Example 4 described above.

[0128] The dielectric loss (DF) was measured by maintaining the normal temperature capacitance of the sample chips of Comparative Example 2 and Example 4 for 60 seconds under the conditions of 1 kHz and 1 Vr using an LCR meter.

[0129]

Table 2

[0130] It was confirmed that the average value of the dielectric loss of Example 4 was about 0.5% lower than the average value of the dielectric loss of Comparative Example 2, and thus it can be confirmed that the dielectric loss characteristics were improved.

[0131] From this, it can be confirmed that the dielectric loss is improved when the number ND of the first dielectric crystal grains included in the capacitance forming portion is greater than the number RD of the second dielectric crystal grains included in the capacitance forming portion, more specifically, when there is a difference of 40%.

[0132] Next, the dielectric capacitance (μF) according to the DC bias voltage was measured for Comparative Example 2 and Example 4. For the samples of Comparative Example 2 and Example 4, AC 1 kHz, 1 Vr conditions were applied for 60 seconds using an LCR meter, and the dielectric capacitance was measured every time the voltage was increased by 1 V. The voltage was increased from 0 V to 10 V, and it can be seen from FIG. 9 that the dielectric capacitance changes based on the dielectric capacitance value at 0 V.

[0133] FIG. 9 is a graph showing the dielectric capacitance (μF) as a function of the DC bias voltage (V) in Comparative Example 2 and Example 4.

[0134] In particular, it can be seen that there is a large difference in dielectric capacitance between Comparative Example 2 and Example 4 under low voltage conditions of 4V or less. This is expected to be because, as the electric field, which is the voltage per unit thickness (V / μm) of the dielectric layer due to the external voltage, becomes stronger at high voltages exceeding 4V, it becomes easier to align the polarization direction in the electric field direction, and they show similar domain characteristics, thereby reducing the difference in the effect of improving the dielectric characteristics due to the domains.

[0135] From this, it can be confirmed that the dielectric capacitance is improved when the number ND of the first dielectric crystal grains included in the capacitance forming portion is greater than the number RD of the second dielectric crystal grains included in the capacitance forming portion under low voltage, more specifically, when there is a difference of 40%.

[0136] Hereinafter, a method for manufacturing a multilayer electronic component will be described, taking a multilayer ceramic capacitor as an example, but the present invention is not limited thereto. Furthermore, in the description of the method for manufacturing a multilayer electronic component according to an embodiment of the present invention, any description that overlaps with the above-mentioned multilayer electronic component will be omitted.

[0137] A method for manufacturing a multilayer electronic component according to an embodiment of the present invention includes providing a slurry containing dielectric powder, a solvent, a dispersant, and a binder, and providing a ceramic green sheet using the slurry; printing and laminating a conductive paste for an internal electrode on the ceramic green sheet to provide a laminated body; firing the laminated body to provide a main body including a dielectric layer containing a plurality of dielectric crystal grains and a capacitance forming portion including internal electrodes laminated alternately with the dielectric layer; and providing external electrodes on the main body. The plurality of dielectric crystal grains include first dielectric crystal grains including nanodomains which are domain regions having a size of 10 nm or more and less than 100 nm, and second dielectric crystal grains including local polarization regions which are domain regions having a size of less than 10 nm. When the number of the first dielectric crystal grains included in the capacitance forming portion is ND and the number of the second dielectric crystal grains included in the capacitance forming portion is RD, 50% < ND / (ND + RD) can be satisfied.

[0138] First, a slurry containing dielectric powder, a solvent, a dispersant, and a binder can be provided, and a step of providing a ceramic green sheet using the slurry can be performed.

[0139] As the dielectric powder, a perovskite (ABO3) - based material can be used. For example, a barium titanate - based material, a lead composite perovskite - based material, or a strontium titanate - based material can be used. The barium titanate - based material can include BaTiO3 - based ceramic powder. Examples of the ceramic powder include BaTiO3, (Ba 1-x Ca x )TiO3 (0 < x < 1) in which Ca (calcium), Zr (zirconium), etc. are partially solid - solved in BaTiO3, Ba(Ti 1-y Ca y )O3 (0 < y < 1), (Ba 1-x Ca x )(Ti 1-y Zr y )O3 (0 < x < 1, 0 < y < 1), or Ba(Ti 1-y Zr y )O3 (0 < y < 1), etc.

[0140] The average diameter of the dielectric powder may be 50 nm or more and 300 nm or less. The dielectric powder may be composed of a plurality of dielectric particles, and the diameter of the dielectric particles may be calculated by averaging the major and minor diameters of the dielectric particles. The average diameter of the plurality of dielectric particles may be the average diameter of the dielectric powder, but is not particularly limited thereto.

[0141] When the average diameter of the dielectric powder is 50 nm or more and 300 nm or less, the nano-domains 21 can be easily generated after sintering, and the effect of improving the dielectric characteristics due to the ratio of the numbers of the first dielectric crystal grains 20 and the second dielectric crystal grains 30 can be more excellent.

[0142] The solvent, dispersant, and binder are not particularly limited and may be any of commonly used substances.

[0143] The prepared slurry is then applied onto a carrier film to provide a ceramic green sheet having a certain thickness.

[0144] Next, a conductive paste for internal electrodes may be printed on the ceramic green sheets and laminated to provide a laminate body.

[0145] The conductive paste may contain a conductive metal. The conductive metal is not particularly limited, but may be a material having excellent electrical conductivity, like the internal electrodes described above.

[0146] More specifically, the internal electrode patterns can be formed by printing the conductive paste for the internal electrodes at a predetermined interval on the ceramic green sheets. For example, a plurality of stripe-shaped first internal electrode patterns can be formed. The plurality of stripe-shaped first internal electrode patterns can be formed parallel to each other, and the ceramic green sheet on which the first internal electrode patterns are formed can be defined as a first ceramic green sheet. A plurality of stripe-shaped second internal electrode patterns can be formed at a predetermined interval on another ceramic green sheet, and the ceramic green sheet on which the second internal electrode patterns are formed can be defined as a second ceramic green sheet.

[0147] The internal electrode pattern may be formed by applying an internal electrode paste onto a ceramic green sheet using a screen printing method, a gravure printing method, or the like, but is not limited thereto.

[0148] A step of stacking and cutting a plurality of ceramic green sheets having a plurality of internal electrode patterns formed thereon to form a laminate body may be performed.

[0149] More specifically, a plurality of stripe-shaped first internal electrode patterns are formed at predetermined intervals on a ceramic green sheet. The plurality of stripe-shaped first internal electrode patterns may be formed parallel to each other, and the ceramic green sheet on which the first internal electrode patterns are formed may be defined as a first ceramic green sheet. Furthermore, a plurality of stripe-shaped second internal electrode patterns may be formed at predetermined intervals on another ceramic green sheet, and the ceramic green sheet on which the second internal electrode patterns are formed may be defined as a second ceramic green sheet.

[0150] In this case, a portion where the ceramic green sheets and the internal electrode patterns are laminated in a first direction to form a capacitance can be defined as a capacitance forming portion, and the green sheets of the cover portion can be disposed on both end faces of the capacitance forming portion in the first direction. More specifically, the green sheets of the cover portion can include a first green sheet of the cover portion disposed on an upper portion of the capacitance forming portion in the first direction and a second green sheet of the cover portion disposed on a lower portion of the capacitance forming portion in the first direction.

[0151] A first ceramic green sheet having a plurality of parallel stripe-shaped first internal electrode patterns printed thereon and a second ceramic green sheet having a plurality of parallel stripe-shaped second internal electrode patterns printed thereon can be alternately stacked to form a ceramic green sheet laminate body.

[0152] The ceramic green sheet laminate body may be cut across the plurality of stripe-shaped first internal electrode patterns and the plurality of stripe-shaped second internal electrode patterns, i.e., the ceramic green sheet laminate body may be cut along cutting lines perpendicular to each other.

[0153] Next, a side margin green sheet can be formed on a side surface in the third direction of the laminated body.

[0154] More specifically, a first side margin green sheet can be formed on one surface in the third direction of the laminate body, for example, the third surface, and a second side margin green sheet can be formed on the other surface in the third direction of the laminate body, for example, the fourth surface.

[0155] Next, a step of firing the laminated body may be performed to provide a body including a capacitance-forming portion including dielectric layers including a plurality of dielectric crystal grains, and internal electrodes laminated alternately with the dielectric layers.

[0156] After the firing process, the striped first internal electrode pattern can become the first internal electrode 121, and the striped second internal electrode pattern can become the second internal electrode 122. Also, the green sheet of the first cover portion can become the first cover portion 112, and the green sheet of the second cover portion can become the second cover portion 113. And the first side margin portion green sheet can become the first side margin portion 114, and the second side margin portion green sheet can become the second side margin portion 115.

[0157] Next, it can include the step of applying an external electrode paste on the main body and firing it to provide the external electrodes 131 and 132.

[0158] More specifically, the first external electrode paste can be applied to one surface of the laminated main body in the second direction, for example, the third surface 3, and after applying the second external electrode paste on the other surface of the laminated main body in the second direction, for example, the fourth surface 4, the first external electrode paste and the second external electrode paste can be fired to form the first external electrode 131 and the second external electrode 132.

[0159] Furthermore, a plating process can be further performed so that the external electrodes 131 and 132 include plating layers 131b and 132b.

[0160] Since the content regarding the external electrodes 131 and 132 is the same as described above, it is omitted.

[0161] On the other hand, the capacitance forming portion of the fired main body can include a plurality of dielectric crystal grains. The plurality of dielectric crystal grains include first dielectric crystal grains including nanodomains which are domain regions having a size of 10 nm or more and less than 100 nm, and second dielectric crystal grains including local polarization regions which are domain regions having a size of less than 10 nm. When the number of the first dielectric crystal grains included in the capacitance forming portion is ND and the number of the second dielectric crystal grains included in the capacitance forming portion is RD, 50% < ND / (ND + RD) can be satisfied.

[0162] The explanation for this is the same as that described for the multilayer electronic component 100 above, and thus will be omitted.

[0163] On the other hand, the firing conditions at the stage of firing the laminated body are as follows.

[0164] When firing the laminated body, it can be carried out in a reducing atmosphere with a hydrogen concentration of less than 0.5%. Here, a hydrogen concentration of less than 0.5% can correspond to a condition of less than 760 mV of EMF.

[0165] When firing is carried out in a reducing atmosphere with a hydrogen concentration of less than 0.5%, the formation of the first dielectric crystal grains 20 containing the nano-domains 21 can be facilitated, and the expression of the first dielectric crystal grains 20 and the second dielectric crystal grains 30 can be easily controlled. Thereby, it is easy to control the ratio of the number ND of the first dielectric crystal grains 20 contained in the capacitance forming portion Ac to the number RD of the second dielectric crystal grains 30 contained in the capacitance forming portion Ac so as to satisfy 50% < ND / (ND + RD).

[0166] The firing temperature can be, for example, a temperature of 1150°C or higher and 1300°C or lower, preferably a temperature of 1200°C or higher and 1250°C or lower, but is not particularly limited thereto.

[0167] As described above, the embodiments of the present invention have been described in detail. However, the present invention is not limited by the above-described embodiments and the accompanying drawings, but is limited by the appended claims. Therefore, within the scope not departing from the technical idea of the present invention described in the claims, various forms of substitution, modification, and change are possible by those having ordinary knowledge in the technical field, and it can be said that these also belong to the scope of the present invention.

[0168] In addition, the expression "one embodiment" used in this specification does not mean the same embodiment, but is provided to emphasize and describe each unique feature that is different from the others. However, the above-mentioned one embodiment does not exclude being realized in combination with the features of another embodiment. For example, even if a matter described in a specific embodiment is not described in another embodiment, it can be understood as a description related to the other embodiment, unless there is a description in the other embodiment that is opposite or contradictory to the matter.

[0169] The terms used in this specification are merely used to describe one embodiment and are not intended to limit the present disclosure. In this case, the singular expression includes the plural expression unless the context clearly indicates otherwise. [Explanation of symbols]

[0170] 10 Dielectric grains 20 First dielectric crystal grain 21 Nanodomain 22 Domain Wall 23 Polarization direction 30 Second dielectric crystal grain 31 Local Polarization Region 33 Polarization direction 100 Multilayer electronic components 110 Main unit 111 Dielectric layer 112, 113 Cover part 114, 115 Side margin 121, 122 Internal electrode 131, 132 External electrode

Claims

1. a main body including a capacitance forming portion including a dielectric layer including a plurality of dielectric crystal grains and an internal electrode alternately laminated with the dielectric layer; an external electrode disposed on the body; The plurality of dielectric crystal grains include first dielectric crystal grains including nano-domains of domain regions having a major diameter of 10 nm or more and less than 100 nm, and second dielectric crystal grains including local polarization regions of domain regions having a major diameter of less than 10 nm; When the number of first dielectric crystal grains included in the capacitance forming portion is ND and the number of second dielectric crystal grains included in the capacitance forming portion is RD, A multilayer electronic component that satisfies 50%<ND / (ND+RD).

2. The multilayer electronic component according to claim 1 , wherein the ND and RD satisfy 66%<ND / (ND+RD).

3. The capacitance forming portion includes a plurality of nano-domains, The multilayer electronic component according to claim 1 , wherein a percentage of a total cross-sectional area of ​​the plurality of nano-domains with respect to a cross-sectional area of ​​the capacitance forming portion is 10% or more.

4. 2. The laminated electronic component according to claim 1, wherein the first dielectric crystal grains include three or more distinct nanodomains and two or more domain walls disposed between adjacent nanodomains, and at least two of the domain walls are not parallel.

5. The laminated electronic component of claim 4 , wherein at least two major diameter directions of a plurality of said nano-domains are non-parallel.

6. The dielectric layer is made of barium titanate (BaTiO 3 2. The multilayer electronic component according to claim 1, comprising a polysilicon-based material as a main component.

7. 2. The multilayer electronic component according to claim 1, wherein an average diameter of the plurality of dielectric crystal grains is not less than 100 nm and not more than 300 nm.

8. the plurality of dielectric crystal grains includes a plurality of first dielectric crystal grains, 2. The multilayer electronic component according to claim 1, wherein an average diameter of the plurality of first dielectric crystal grains is not less than 100 nm and not more than 300 nm.

9. 2. The laminated electronic component according to claim 1, wherein a percentage of a major diameter of one of the nano-domains to a diameter of one of the first dielectric crystal grains is 26% or more.

10. 10. The multilayer electronic component according to claim 1, wherein the dielectric layers have an average thickness of 0.6 μm or less.

11. 10. The multilayer electronic component according to claim 1, wherein the length of the multilayer electronic component is 0.6 mm or less and the width of the multilayer electronic component is 0.3 mm or less.

Citation Information

Patent Citations

  • WOPWO2013-146303